FRI0558 PREVALENCE OF SUBCLINICAL SACROILIITIS IN YOUNG PATIENTS WITH INFLAMMATORY BOWEL DISEASE REVEALED BY ENTERO-MRI. (June 2019) - Giani, Teresa; Filistrucchi, Viola; Basile, Massimo; Perrone, Anna; Maurizio, Marco DI; Bernardini, Azzurra; Renzo, Sara; Lionetti, Paolo; Cimaz, Rolando
Abstract : Background: Sacroiliitis is one of the extraintestinal manifestations associated with inflammatory bowel disease (IBD), and may be underdiagnosed especially in the pediatric age. MR-enterography (Entero-MRI) is currently the imaging gold standard to assess intestinal disease activity and to detect complications in patients with IBD. Only few studies have been conducted on adult patients with IBD in order to define the role of this technique in assessing sacroiliitis, while no data are available on pediatric patients. Objectives: To study the prevalence of inflammatory sacroiliitis on MRI performed for intestinal investigation in an IBD pediatric population. Methods: This is a retrospective study conducted on patients suffering from IBD followed in our gastroenterology department between 2010 and 2018 whose entero-RM (1.5 or 3 Tesla, Philips depending from year of scanning) were blindly and independently scored by two readers experienced in pediatric musculoskeletal imaging. Each sacroiliac joint was divided into 4 quadrants. Signs of sacroiliitis were identified according to the ASAS criteria, with a particular attention to the presence of bone marrow edema (using T2 weighted sequences with fat suppression), diffusion restriction in DWI sequences (Diffusion Weighted Imaging) or DWIBS (Diffusion Weighted Imaging with Background Suppression) and post-contrastographic uptake in dynamic acquisitions. Demographics, IBD characteristics, clinical, radiological, and laboratory data were recorded and a dedicated Excel database was constructed. Results were elaborated using descriptive statistics. Results: 34 patients (10 F, 24 M, age at scanning range 5-20 yrs, median 15) were included in the study, for a total of 59 entero-MRI evaluated (some patients were subjected to more than one scan). Two out of 34 patients were affected by Ulcerative Colitis, 32 by Crohn disease. Joint examination resulted negative in all patients, and none complained of articular symptoms including back pain. In 5 IBD patients (4 CD, 1 UC) a monolateral slight degree of sacroiliitis (grade 1) was radiologically identified. They were all males, without clinical-laboratory-radiologic inflammatory signs of intestinal activity, with the exception of a patient who presented signs of intestinal and sacroiliac inflammation at his first entero-MRI, while 18 months later, at his MRI control under pharmacological treatment, signs of sacroiliitis were still present in the absence of intestinal signs of inflammation. Conclusion: Asymptomatic sacroiliitis was observed in about 15% of our IBD patients. Sacroiliac involvement therefore can be underdiagnosed in these patients. Entero-MRI with specific sequences could be a good tool to detect early signs of sacroiliac inflammation. References: [1] S.Lecler-Jacob, G.Lux, A.C.Rat, V.Laurent, A.Blum, I. Chary-Valckenaere, L.Peyrin-Biroulet & D. Loeuille. The prevalence of inflammatory sacroiliitis assessed on magnetic resonance imaging of inflammatory bowel disease: a retrospective study performed on 186 patients. Aliment Pharmacol Ther 2014; 39: 957-962. [2] Timothy J.P. Bray, Nicola Ambrose, David Atkinson, Debajit Sen, Yiannis Ioannou and Margaret A. Hall-Craggs Diffusion-weighted imaging is a sensitive biomarker of response to biologic therapy in enthesitis-related arthritis. Rheumatology 2017; 56: 399-407. Disclosure of Interests: None declared